2002
DOI: 10.1039/b210337k
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the hydrothermal stability of SAPO-34

Abstract: Hydrothermal stability of SAPO-34 is greatly improved by the treatment of the acidic form of the SAPO-34 with NH3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 3 publications
2
22
0
Order By: Relevance
“…This behavior was already reported in the literature for more conventional SAPO-34 samples [22][23][24][25]. Briend et al [22] related the lack of long-term stability to the presence of silicon islands, favored by the use of morpholine as template.…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…This behavior was already reported in the literature for more conventional SAPO-34 samples [22][23][24][25]. Briend et al [22] related the lack of long-term stability to the presence of silicon islands, favored by the use of morpholine as template.…”
Section: Introductionsupporting
confidence: 59%
“…Briend et al [22] related the lack of long-term stability to the presence of silicon islands, favored by the use of morpholine as template. Other authors [23,26] showed that the structural deterioration can be prevented if after removing the template the acid sites are covered with ammonia.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Janssen et al [8] proposed methods to inhibit the skeleton collapse of SAPO molecular sieve by using templates and carbonaceous material to shield the catalytic sites from contacting with H 2 O molecules. Mees et al [9] found that the hydrothermal stability of SAPO-34 was greatly improved by replacing the hydroxyl groups by amino species. These modification methods may be applied for the process of methanol to olefins (MTO); however, they are not practical for Cu/SAPO-34 catalysts during SCR process as hydrothermal exposure cannot be avoided in vehicle exhaust.…”
Section: Introductionmentioning
confidence: 99%
“…For used Cu-SAPO-34, the intensity of all diffraction peaks decreased significantly. The XRD patterns showed that the crystalline structure was changed by the action of H 2 O [11,19]. However, there was no evident decline of crystallinity for the used CuCe 0.06 -SAPO-34 sample compared to the fresh one.…”
Section: Catalytic Activitymentioning
confidence: 90%
“…This indicated that Ce ions may replace the proton of the Si\ \O(H)\ \Al bond to decrease the concentration of Si\ \O(H)\ \Al bonds, preventing the hydrolysis reactions at the acid sites [11,20]. The interaction of H 2 O with other framework atoms appeared to be much weaker and was reversible, improving the stability of the zeolite [19]. The higher stability of the CHA structure in CuCe 0.06 -SAPO-34 contributed to its higher water resistance in comparison with Cu-SAPO-34.…”
Section: Catalytic Activitymentioning
confidence: 99%